Recombinant PhpA Protein, a Unique Histidine Motif-Containing Protein from Streptococcus pneumoniae, Protects Mice against Intranasal Pneumococcal Challenge - Zhang, Ying (American Society for Microbiology, 2001)
The multivalent pneumococcal conjugate vaccine is effective against both systemic disease and otitis media caused by serotypes contained in the vaccine. However, serotypes not covered by the current conjugate vaccine may still cause pneumococcal disease. To address these serotypes and the remaining otitis media due to Streptococcus pneumoniae, we have been evaluating antigenically conserved proteins from S. pneumoniae as vaccine candidates. A previous report identified a 20-kDa protein with putative human complement C3-proteolytic activity. By utilizing the publicly released pneumococcal genomic sequences, we found the gene encoding the 20-kDa protein to be part of a putative open reading frame of approximately 2,400 bp. We recombinantly expressed a 79-kDa fragment (rPhpA-79) that contains a repeated HxxHxH motif and evaluated it for vaccine potential. The antibodies elicited by the purified rPhpA-79 protein were cross-reactive to proteins from multiple strains of S. pneumoniae and were against surface-exposed epitopes. Immunization with rPhpA-79 protein adjuvanted with monophosphoryl lipid A (for subcutaneous immunization) or a mutant cholera toxin, CT-E29H (for intranasal immunization), protected CBA/N mice against death and bacteremia, as well as reduced nasopharyngeal colonization, following intranasal challenge with a heterologous pneumococcal strain. In contrast, immunization with the 20-kDa portion of the PhpA protein did not protect mice. These results suggest that rPhpA-79 is a potential candidate for use as a vaccine against pneumococcal systemic disease and otitis media.